A descriptive study of acutely poisoned patients presenting to the Western Cape Emergency Medical Services - Moreira, Fabio (Division of Emergency Medicine, 2026)
Background: The scale and types of acute poisoning presenting to the prehospital provider in South Africa and other low- or middle-income countries is largely unknown. Emergency medical services (EMS) are often responsible for the on-scene management and transport of these patients and have a range of treatment options depending on scope of practice. The aim of this study was to describe acute poisoning patients presenting to the Western Cape Government Health and Wellness EMS. Methods: A retrospective descriptive study was conducted utilizing electronic patient care data of acute poisoning cases extracted from EMS records for the calendar year 2022. Results: Of the 2254 acute poisoning cases identified, 69.03% were female. The median age was 27 years, and the method of poisoning was most commonly ingestion (97.20%). A single toxin was involved in 46.85% of cases, while 32.03% of cases involved multiple toxins. In 34.38% of all cases, a toxin unknown to EMS was reported. Paracetamol and alcohol were the most common known toxins observed. The top 5 toxins by single toxin involvement were herbicides and pesticides; antiretrovirals; antiseptics and disinfectants; paracetamol; and hydrocarbons. There were a higher number of cases in the second half of the year, with a peak in November and December, as well as more cases. during weekends. Most cases were triaged as moderate to severe acuity. Activated charcoal was administered in 3.46% of cases; oxygen was administered in 3.82% of cases; intravenous access was obtained in 17.7% of patients and 1.97% of cases had a documented airway intervention performed. Conclusion: There is a necessity for better awareness, and improved training for EMS providers to enhance the care of acute poisoning patients. Further research is warranted to investigate the gaps in management and the implications for patient outcomes, ultimately contributing to the development of effective interventions and educational programs aimed at reducing the incidence and severity of acute poisoning.